2012
DOI: 10.1002/nau.22350
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the phytotherapeutic agent eviprostat on the bladder in a rat model of bladder overdistension/emptying

Abstract: Eviprostat-mediated suppression of increased bladder oxidative stress and inflammation caused by bladder OE may contribute to the improvement of BBF and bladder function by Eviprostat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 23 publications
4
18
0
Order By: Relevance
“…In one model, we subjected rats to continuous bladder distension for 2 h followed by emptying and noted that BBF decreased progressively after emptying. This result is consistent with our previous finding of a decreased BBF the day after the induction of bladder O/E (Kawai et al, 2013). In this model, we found that intraduodenal administration of tadalafil significantly blocked the progressive O/ E-induced reduction in BBF.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In one model, we subjected rats to continuous bladder distension for 2 h followed by emptying and noted that BBF decreased progressively after emptying. This result is consistent with our previous finding of a decreased BBF the day after the induction of bladder O/E (Kawai et al, 2013). In this model, we found that intraduodenal administration of tadalafil significantly blocked the progressive O/ E-induced reduction in BBF.…”
Section: Discussionsupporting
confidence: 93%
“…These findings indicate that bladder ischemia is a key mechanism underlying symptoms that are associated with BPH. Although the decreased BBF observed in our acute rat model may not reflect exactly the chronic decrease in BBF in human BPH, bladder O/E carried out under conditions similar to those of our model have been used by us and others to study the effect of drugs on BBF and bladder dysfunction (Kawai et al, 2013;Okutsu et al, 2011). Therefore, it is likely that tadalafil increased the blood supply and reduced the bladder ischemia caused by BOO.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The bladder was exposed and emptied by inserting a catheter through the urethra. After removing the catheter, the BBF was determined with a laser speckle blood flow imager (Omegazone OZ-1; Omegawave, Tokyo, Japan) as described by Oka et al [7]. For measurement, the bladder surface was diffusely illuminated with a 780-nm semiconductor laser, scattered light was filtered with a hybrid filter and detected by a charge-coupled-device (CCD) camera, and the images were transferred to a computer for analysis.…”
Section: Measurement Of Bladder Blood Flow (Bbf)mentioning
confidence: 99%